Prospects of using microalgae for biofuels production: Results of a Delphi study - Teresa M. Mata (2015)
Advanced biofuels, such as those obtained from microalgae, are widely accepted as better choices for achieving goals of incorporating renewables and non-food fuel sources into the transportation sector, and for overcoming land use issues due to biofuel crops. Main challenges are currently the feasibility of large-scale commercialization of microalgae biofuels, since there are still some technical problems to overcome (e.g. the high energy consumption associated with biomass processing) and the majority of economic and financial analyses are based on pilot-scale projects. Therefore, this article presents the results of a Delphi study aiming to identify the main obstacles and most critical issues affecting the potential of large-scale commercialization of microalgae biodiesel and its incorporation into the fuel market. According to the authors' knowledge, this is the first Delphi study with this objective. The respondents are worldwide market specialists in the survey themes that ranged from biofuels economics to their environmental sustainability. One of the key findings is that most of the experts believe that production of microalgae biofuels will achieve its full commercial scale until 2020, and that from 2021 till 2030 it could represent from 1% to 5% of the worldwide fuel consumption. The study results also showed that environmental issues are where expert opinion differs more.